2018
DOI: 10.1039/c8en00751a
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and movement of hydroxyapatite nanoparticles (HA-NPs) applied as a phosphorus fertiliser in soils

Abstract: Hydroxyapatite nanoparticles pose as a novel P fertiliser in acid soils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 35 publications
3
45
0
Order By: Relevance
“…The results showed that in the experimental conditions, the P uptake and the percentage of P in the plant that was derived from the fertilizer followed the order: TSP > nHAP > bulk HAP (Table 1). A second experiment dedicated to studying the behavior of nHAP in soil was carried out by Xiong et al [54]. In this case, three forms of nHAP having different surface charges (positive, neutral, and negative) were administered to Helianthus annuus grown in P deficient Ultisol and Vertisol, respectively.…”
Section: Nano-hydroxyapatite As Source Of Phosphorusmentioning
confidence: 99%
“…The results showed that in the experimental conditions, the P uptake and the percentage of P in the plant that was derived from the fertilizer followed the order: TSP > nHAP > bulk HAP (Table 1). A second experiment dedicated to studying the behavior of nHAP in soil was carried out by Xiong et al [54]. In this case, three forms of nHAP having different surface charges (positive, neutral, and negative) were administered to Helianthus annuus grown in P deficient Ultisol and Vertisol, respectively.…”
Section: Nano-hydroxyapatite As Source Of Phosphorusmentioning
confidence: 99%
“…In view of their reported benefits, their use appears to be justified. Relatively few studies investigated the addition of ENMs to soil, however, tested materials include those which are already used in outdoor settings (i.e., CB and hydroxyapatite) [55,77] and those which are prone to dissolution and are commonly used in conventional agriculture in dissolved form (i.e., Cu and Zn) [27,62,70,72,78]. This suggests that such uses are also justified from a nanosafety perspective.…”
Section: Applications Of Enms In the Agri-food Sectormentioning
confidence: 99%
“… 11 Many researchers have formulated slow-release fertilizers by incorporating hydroxyapatite (HA) and urea to increase delivery of nutrients to the plants. 12 − 14 In this background, we report here a hybrid nanofertilizer (HNF) composition with some extension, which is made by incorporating nanourea-modified hydroxyapatite nanoparticles into copper, iron, and zinc nanoparticles. A hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 ) nanoparticle is a continuous source of calcium and phosphate micronutrients, and it is used in surface modification for the formation of nanohybrids.…”
Section: Introductionmentioning
confidence: 99%